Unlocking creativity : how to solve any problem and make the best decisions by shifting creative mindsets - Roberto, Michael A. (Gildan, 2019)
Leaders do not have to conceive innovative ideas, but rather open the path for curious and creative employees within their organization. Unlocking Creativity: How to Solve Any Problem and Make the Best Decisions aids organizations in removing obstacles to the creative process and helps to form an atmosphere of imagination and innovation.